The myth of the creation of the universe, man and animals in the Islamic East from the perspective of Muslim geographers (Al-Masudi and Al-Bayruni) as an example - كانبی, ا.د.صلاح كانبی اسماعيل; بکر, م.م.شیما بکر عبدالله (Sulaimani Journal for Humanities, 2025)
Since creation began, myths had accompanied all stages of human life, even in this era of the tremendous scientific and technological developments many people still believe in them. Every myth contains a set of beliefs, sayings, and proverbs that represent its owners, that is, different peoples of the world who believe in it, as each people has its own myths, and even the peoples that have reached the pinnacle of civilizational progress, have their own myths and beliefs, as backward nations do. On this basis, we can define myth as a means of expressing the desires and ideas that lie within the human soul, and the images that appear as a result of the motives that deeply lie inside the mankind soul, which in turn stimulate and arouse human ideas, which are generally similar to what happens to someone whenever he sees many images that may embody in his mind through the dreams he may see when sleeping, which eventually turn into some kind of stories. In any case, myths represent a large part of any people’s heritage that passes down from generation to generation, so deeply that will become embedded in their souls and minds in such a way that they become an effective aspect of the intellectual and spiritual structure that dominates many aspects of people's public life. Surely, these myths have some real foundations, but over time, human thoughts have given them an imaginative character, making them far from truth and reality. In general, mythical characters in any people's legends include very similar models, as they generally about creative divine figures, heroes with supernatural powers, or romantic characters immersed in matters of love and passion. Sometimes, they may include comedic or moral characters. However, the oldest mythical figures created by human thoughts and imagination were the divine figures capable of creation. This is why we see many myths and legends that depict and tell the story of the emergence of man, as well as imaginary stories that describe how the earth and sky emerged and then how other beings of all kinds and different forms, especially the human being had emerged and inhabited the earth. This research consists of a summary (Also available in Arabic and English), then an introduction, followed by the three main topics of the research. Finally, the results, footnotes, and a list of research sources are introduced. The first topic is devoted to defining the concept of myth; the second topic discusses the myth of creation (creation of the universe, the man and animals). The third and final topic, presents the impact and consequences of the creation myth on society.
Keywords: Myth; Universe; Human and Animal; Influence